Digital Campaign to Combat Violence and Sexual Harassment: Advancing Gender Equality for All Women and Girls - Fitri, Wahyu; Zumiarti, Zumiarti; Surya, Rahmad; Wijaya, Anggi Hadi (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effectiveness of digital campaigns in increasing public awareness about gender equality and reducing the incidence of violence and sexual harassment against women and girls. By leveraging social media platforms and online media, digital campaigns can be a powerful tool for mobilizing public opinion and driving the necessary social change. The research approach used is a mixed method which includes in-depth interviews with 30 interviewees and the distribution of 200 questionnaires to the community in West Sumatra, one of the regions with the highest incidence of sexual violence in Indonesia (qualitative-quantitative). The data was analyzed using Nvivo 12+ software and Smart PLS so that comprehensive and valid results were obtained. This research shows that digital campaigns have great potential to influence people's attitudes towards gender issues, increase understanding of gender equality, and help reduce the rate of sexual violence and harassment. The study provides recommendations for policymakers and stakeholders to increase the adoption and use of digital campaigns as a key strategy to achieve gender equality and protect women and girls from violence.